Manajemen Syok Hipovolemia pada Pasien Fraktur Patologis Neck-Femur Suspek Metastasis dengan Hemiarthroplasty: Studi Kasus - Retnaningsih, Retnaningsih; Triyanto, Arifin; Subekti, Tri (PSIK FKKMK UGM, 2024)
Background: Hemiarthroplasty in a pathological neck-femur fracture of suspected Metastatic Bone Disease (MBD) case, increases the risk of intraoperative bleeding and hypovolemic shock. Case studies related to this phenomenon are scarce.Objective: Describe the management of hypovolemic shock in pathological neck-femur fracture patient with MBD suspect which was followed by hemiarthroplasty action.Case Report: A 59-year-old woman experienced bleeding of 1,000-1,300 cc during surgery, causing shock with low blood pressure, tachycardia, and cold acral. Management of hypovolemic shock during surgery included fluid resuscitation, administration of vasopressors, blood transfusion, and administration of tranexamic acid.Outcome: Hypovolemic shock management course of action was include hemodynamic and coagulation management, with the collaboration of a team of nurses and doctors. The role of instrument, circular, and anesthesia nurses was crucial to maintain patient stability during surgery. After being given management intervention hypovolemic shock, the patient's response to resuscitation therapy was in a fast category so that the shock was quickly resolved and the operation could be continued until completion.Conclusion: Monitoring and rapid treatment of shock in pathological neck-femur fracture patient with MBD suspect which is followed by hemiarthroplasty action, including intraoperative bleeding, can prevent morbidity and mortality.INTISARILatar belakang:Hemiarthroplasty pada fraktur patologis neck-femur suspek Metastatic Bone Disease (MBD) meningkatkan risiko perdarahan intraoperatif dan syok hipovolemia. Studi kasus terkait hal ini masih jarang ditemukan. Tujuan: Mendeskripsikan tata laksana manajemen syok hipovolemia pada pasien fraktur patologis neck-femur suspek mengalami MBD untuk kemudian mendapatkan tindakan hemiarthroplasty.Laporan kasus: Wanita 59 tahun mengalami perdarahan 1.000-1.300 cc selama operasi, menyebabkan syok dengan tekanan darah rendah, takikardi, dan akral dingin. Manajemen syok hipovolemia selama operasi, meliputi resusitasi cairan, pemberian vasopressor, transfusi darah, dan pemberian asam traneksamat.Hasil:Tindakan manajemen syok hipovolemia meliputi manajemen hemodinamik dan koagulasi, dengan kolaborasi tim perawat dan dokter. Peran perawat instrumen, sirkuler, dan anestesi penting untuk menjaga stabilitas pasien selama operasi. Setelah diberikan intervensi manajemen syok hipovolemia, respons pasien terhadap terapi resusitasi termasuk katagori cepat, sehingga syok segera teratasi dan operasi dapat dilanjutkan sampai selesai.Simpulan:Monitoring dan penanganan syok secara cepat pada pasien fraktur patologis neck-femur yang dilakukan tindakan hemiarthroplasty dengan perdarahan intraoperatif dapat mencegah morbiditas dan mortalitas.